The Impact of the Strategies of Resistance to Change Management on the Improvement of Workers Performance (Case Study of the Jordanian Telecommunications Companies) (Global Journal of Management and Business Research, 2017)
The study aimed to identify the impact of strategies of change resistance management on the improvement of the performance of workers in the Jordanian telecommunications companies, the study population consists of all the workers of these companies. The questionnaire was distributed to a sample of (225) Single eatery, including staff at the center and branches, (212) of distributed questionnaires which they form the percentage of (95%) of the number has been collected, (205) questionnaire of them underwent statistical analysis, representing (87%) of the number of questionnaires received. There is a statistically significant between the resistance to organizational change management strategies and the improvement of the performance of workers in Jordanian companies, in light of the results of the study the researcher presented some recommendations: the need to satisfy the psychological and physical needs, allow workers to participate effectively in change programs, build a supportive organizational culture processes for organizational change, application of training programs on the importance of managing change.
Keywords: strategy; change; management of resistance to change; the performance of workers